Research on the Pathway to Cultivating College Students’ Innovation and Entrepreneurship Abilities in a Digital Context - You, Ren (International Journal of Computer Science and Information Technology, 2024)
In the context of accelerating globalization and digitization, the innovation and entrepreneurship abilities of college students have become vital for driving economic and social development. This paper explores how higher education institutions can cultivate these abilities in a digital environment, analyzes the contradictions between the current educational system and market demand, and proposes targeted solutions. The research indicates that utilizing advanced technologies such as artificial intelligence, big data, and online learning platforms is steering innovation and entrepreneurship education in universities towards a more personalized and diversified approach. A new theoretical model is constructed that emphasizes the significance of digital educational tools, personalized learning paths, and evaluation systems. Furthermore, specific recommendations for educational policymakers, higher education institutions, and educational technology developers are summarized. This study provides theoretical support and practical guidance for digital innovation and entrepreneurship education, aiming to enhance college students’ overall quality and their ability to face future challenges.